Changes in the body weight of term infants, born in the tropics, during the first seven days of life. - Turner, C; Carrara, V; Thien, N; Paw, N; Rijken, M; Mcgready, R; Nosten, F (BioMed Central, 2013)
BACKGROUND: Identifying unwell neonates, particularly in the first week of life, is often subjective. If normal values are known, calculating the weight lost or gained from birth weight can be a useful adjunct in the evaluation of the health of a neonate. METHODS: Serial body weights of well, term, breast fed infants who were attending for routine follow up, were recorded at the Shoklo Malaria Research Unit clinic in Maela Camp for displaced persons on the Thailand Myanmar border. Newborn examination was routine. Weight loss, expressed as percent weight lost from birth weight, and weight gain, expressed as a velocity (g/kg/day), was calculated for the first seven days of life. The results from normal birth weight infants, low birth weight infants (<2.5 kg) and small for gestational age infants (SGA) were examined. RESULTS: In the first week of life there were no significant differences in weight gained or lost across the three study groups. The maximum weight lost was 4.4% (95% CI 4.1 - 4.6%), which occurred on day three. Weight gain ranged from 13 g/kg/day [95% CI 10 - 16] on day four to 18 g/kg/day [95% CI 15 - 20] on days six and seven. CONCLUSIONS: Use of these normal values for weight gain and loss, allows infants falling outside of the expected range (95% CI) to be easily identified and subsequently highlighted as needing further medical review.